Marketing Mix Strategy Formulation of Ready Meal Business using Hierarchical Clustering (Case Study of Kokikit) - Sasti Pretita; Mohamad Toha (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2022)
Kokikit is a food and beverage startup company providing non-frozen ready meal, such as instant rice and instant side dish which is ready to serve within minutes. Although the market growth of ready meal in Indonesia is positive, the revenue of Kokikit keeps decreasing. Marketing is one of the ways to dominate the market share, yet Kokikit has not fully utilised its potential to market the products, which impacted the sales due to its ineffectiveness. The research aims to determine the new segment, target customers and positioning (STP) for Kokikit based on cluster generated from the consumer analysis, and to propose marketing strategies based on new marketing mix according to the cluster’s preferences. The data collection used qualitative method through one-on-one interview with 5 potential consumers to determine attributes, and quantitative method through questionnaire attended by 149 potential consumers within Jabodetabek area, which further analysed using hierarchical clustering. The conclusion of the hierarchical clustering is using Importance-Performance analysis as a comparison between the importance of attributes and its performance in the company. The new target consumers are the ones that prefer hygiene, good taste, variety of menu; price discounts; distribution place using GoFood, GrabFood, supermarkets, or minimarkets; and promotions through YouTube, endorsement and social ads. Therefore, the proposed marketing strategies are maintenance of taste and hygiene, add more variety of menu, conduct more price discounts, opening GoFood and GrabFood, partnering with supermarket and minimarket, conduct regular promotions focusing on YouTube with endorsement and social ads to attract more customers.